2014
DOI: 10.1177/2167702614542280
|View full text |Cite
|
Sign up to set email alerts
|

Threat of Death and Autobiographical Memory

Abstract: We investigated autobiographical memory in a group of passengers onboard a trans-Atlantic flight that nearly ditched at sea. The consistency of traumatic exposure across passengers, some of whom developed post-traumatic stress disorder (PTSD), provided a unique opportunity to assess verified memory for life-threatening trauma. Using the Autobiographical Interview, which separates episodic from non-episodic details, passengers and healthy controls (HCs) recalled three events: the airline disaster (or a highly n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 102 publications
(164 reference statements)
2
45
0
1
Order By: Relevance
“…Specifically, a low number of internal details may suggest a basic deficit in detail construction and/or binding and may be the source of the episodic prospection deficit in MTL amnesia (Mullally, Hassabis, & Maguire, 2012;Rosenbaum et al, 2009;Verfaellie, Race, & Keane, 2012). In contrast, an abnormally high number of external details may reflect executive difficulties involving inhibitory cognitive control, suppression of task-irrelevant thought, or sustained attention (McKinnon et al, 2014), or may simply reflect age-related changes in narrative style, especially in the case of healthy ageing (see Schacter, Gaesser, & Addis, 2012 for discussion). As noted, there are conditions in which both low internal and high external detail generation co-occur, but distinct patterns among clinical populations suggest that they reflect a simultaneous breakdown of dissociable processes.…”
Section: Discussionmentioning
confidence: 89%
“…Specifically, a low number of internal details may suggest a basic deficit in detail construction and/or binding and may be the source of the episodic prospection deficit in MTL amnesia (Mullally, Hassabis, & Maguire, 2012;Rosenbaum et al, 2009;Verfaellie, Race, & Keane, 2012). In contrast, an abnormally high number of external details may reflect executive difficulties involving inhibitory cognitive control, suppression of task-irrelevant thought, or sustained attention (McKinnon et al, 2014), or may simply reflect age-related changes in narrative style, especially in the case of healthy ageing (see Schacter, Gaesser, & Addis, 2012 for discussion). As noted, there are conditions in which both low internal and high external detail generation co-occur, but distinct patterns among clinical populations suggest that they reflect a simultaneous breakdown of dissociable processes.…”
Section: Discussionmentioning
confidence: 89%
“…The Yerkes-Dodson Law has been criticized because it is difficult to falsify (Neiss, 1988): Every finding (of impaired or enhanced memory) can be interpreted as falling on either end of the U-curve, without being able to independently predict where exactly on the curve one falls. Furthermore, indices of arousal do not correlate with each other; and memories for highly-arousing events (e.g., a near plane crash) can be recalled in great detail and last for many years, contrary to the prediction that extreme levels of arousal impair memory (McKinnon et al, 2015). Still, there is overwhelming evidence that moderate levels of arousal enhance memory (Kensinger, 2004;.…”
Section: Emotional Enhancement Of Memory (Eem)mentioning
confidence: 91%
“…Considering these complications, it is perhaps remarkable that a clear picture of emotion's influence on memory in the real world is emerging: Similar to the laboratory, emotional memories are often more detailed and strong than neutral ones. Strongly negative experiences can lead to vivid, long-lasting memories: In one of the few studies able to verify memory reports objectively for accuracy, McKinnon et al (2015) found that passengers aboard a trans-Atlantic flight retained clear, detailed memories of their near-crash into the ocean.…”
Section: Autobiographical Memorymentioning
confidence: 99%
“…Traumatiske minner synes heller ikke å vaere svakere eller dårligere enn mer emosjonelt nedtonede minner (11,13). Dette gjelder også for mer personlige opplevelser (14). En studie av kvinner som hadde vaert utsatt for sterkt traumatiske seksuelle erfaringer, finner at deltagernes hukommelse for de traumatiske erfaringene var meget god, og at minnene fremstår som detaljerte og ordnede (15).…”
Section: Hva Sier Forskning?unclassified